Insect proteins as emulsifiers in oil-in-water emulsions - McColm, Christopher (2023)
Insect protein was extracted using an alkaline extraction method with an ethanol defatting step from six species and two life stages of commercially available insect species. The protein extracts and whole insect powders were analysed for composition and protein structure, oil-in-water emulsions were produced from the protein extracts at 0.44 % protein with a sunflower oil dispersed phase.